Fractional sliding mode control of underwater ROVs subject to non-differentiable disturbances - Muñoz-Vázquez, Aldo-Jonathan; Ramírez-Rodríguez, Heriberto; Parra-Vega, Vicente; Sánchez-Orta, Anand (International journal of control, automation, and systems, 2017)
Some hydrodynamic phenomena of an underwater Remotely Operated Vehicle ( ROV ), such as turbulence, cavitation, and multi-phase fluidic regimes, are associated to continuous but nowhere differentiable functions. These disturbances stand as complex forces potentially influencing the ROVs during typical navigation tasks. In this paper, the tracking control of a ROV subject to nonsmooth Hölder disturbances is proposed based on a fractionalorder robust controller that ensures exponential tracking. Notably, the controller gives rise to a closed-loop system with the following characteristics: a) continuous control signal that alleviates chattering effects; b) the fractional sliding motion is substantiated on a proposed resetting memory principle; c) the control is robust to model uncertainties; and d) exact rejection of Hölder disturbances in finite-time. A representative simulation study reveals the feasibility of the proposed scheme.